2022
DOI: 10.1108/mrr-08-2021-0605
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive job crafting: an intervening mechanism between intrinsic motivation and affective well-being

Abstract: Purpose Employees often reframe their work roles and ascribe meaning to their jobs, which is called cognitive job crafting (CJC). Although scholars have identified the importance of CJC, there remains a lack of evidence on what motivational characteristics affect initiating such cognitive changes and how these cognitive changes affect one’s well-being. Drawing on job design and self-determination theories, this study aims to investigate how intrinsic motivations affect CJC and, thus, optimize affective well-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…We then proposed that job crafting is positively related to occupational well-being. Through the job crafting process, individuals can enhance the meaning they attain from their work and in turn optimize their well-being [ 19 ]. There is already abundant evidence to support this relationship.…”
Section: The Mediation Role Of Job Craftingmentioning
confidence: 99%
“…We then proposed that job crafting is positively related to occupational well-being. Through the job crafting process, individuals can enhance the meaning they attain from their work and in turn optimize their well-being [ 19 ]. There is already abundant evidence to support this relationship.…”
Section: The Mediation Role Of Job Craftingmentioning
confidence: 99%
“…Hence, future research could explore further the obstacles and compromises individuals encounter, offering a more detailed comprehension of the intricacies involved in fostering sustainable career development. Additionally, considering job crafting as a proactive strategy linked to improved individual well-being and productivity indicators [63,64], future research could also investigate the combined effects of crafting initiatives at both job and career levels on the sustainability of individuals' careers [65].…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In the current job‐crafting literature, compared with other job‐crafting types, less attention has been paid to the cognitive job crafting (Zhang & Parker, 2019). The extant literature has found that social support, job characteristics and personal resources (e.g., organizational support, job autonomy, self‐determination, job meaningfulness, job insecurity, recovery experience and creative self‐efficacy) are positively related to the cognitive job crafting (Buonocore et al., 2020; Hur & Shin, 2023; Kilic & Kitapci, 2023; Kim et al., 2018). According to the W–HR theory, the contextual resources, such as social support, will lead to the generation of personal resources (Ten Brummelhuis & Bakker, 2012).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In our study, the employed partner can use the personal resources (e.g., positive affect) generated from the work–family support to cognitively change their view of the job. Moreover, work–family support can help the partner to achieve a balance between work and life and enhance the feeling of meaningfulness at work (Cohen‐Meitar et al., 2009; Munn, 2013), which could allow the partner to have a positive view of their job (Kilic & Kitapci, 2023).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%